2018
DOI: 10.1051/matecconf/201815005011
|View full text |Cite
|
Sign up to set email alerts
|

Examining The Relationships between Attitude Towards Behaviour, Subjective Norms and Entrepreneurial Intention among Engineering Students

Abstract: Abstract. The purpose of this research is to investigate the relationships between attitude towards behaviour, subjective norm and entrepreneurial intention among engineering students from Public Higher Educational Institution (PHEI) in Malaysia. This research is carried out by using the quantitative method (questionnaire). Data are gathered from 345 respondents which consisted of the final year students from one PHEI in Malaysia. Results presented that entrepreneurial intention are positively associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…The findings of this study further strengthen the results of previous studies where the education level of Commerce teachers is at a moderately high level [60]. Similarly, the findings of [61] explains that teachers play a role in influencing students' entrepreneurial careers. Meanwhile, the findings of a study by Zulfaka [62] provide better findings where it was shown that teachers' guidance on entrepreneurship is high.…”
Section: What Is the Level Of Attitude Interest Teachers' Guidancesupporting
confidence: 87%
“…The findings of this study further strengthen the results of previous studies where the education level of Commerce teachers is at a moderately high level [60]. Similarly, the findings of [61] explains that teachers play a role in influencing students' entrepreneurial careers. Meanwhile, the findings of a study by Zulfaka [62] provide better findings where it was shown that teachers' guidance on entrepreneurship is high.…”
Section: What Is the Level Of Attitude Interest Teachers' Guidancesupporting
confidence: 87%
“…Thus, if selfemployment is more appealing to students, their intention to work for themselves will be high and vice versa (Ismail et al, 2013;Majogoro & Mgabo, 2012). The empirical literature has found a positive and significant association between attitude and self-employment intentions(See; Alharbi, Almahdi, & Mosbah, 2018;Ayalew & Zeleke, 2018;Mahendra, Djatmika, & Hermawan, 2017;Mijoč et al, 2016;Saraih, Aris, Mutalib, Ahmad, & Amlus, 2018). On this background, the study proposes that H1:…”
Section: Literature Reviewmentioning
confidence: 89%
“…Our results concur with the findings of earlier studies. For example, Alharbi et al, (2018); Saraih et al, (2018) demonstrates that attitude towards behavior is the main predictor of self-employment intentions. Similarly, Robledo, Arán, Sanchez, and Molina (2015) present that Spanish university students with a positive attitude towards creating a new firm were inclined to become entrepreneurs once they completed their studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the subjective norm is an individual's beliefs of close third parties if they deliberate about behavior; such beliefs are formulated through social pressures, that is, they are elements that evaluate the approval of other people, which can be mainly from family, friends and other role models (Conner, 2020;Saraih et al, 2018). Shi et al (2020) consider that the norms, values, and beliefs of the individual's family environment affect the creation of new businesses.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%